An Effective Approach for Controller Placement in Software‐Defined Internet‐of‐Things (SD‐IoT) - Ali, Jehad; Roh, Byeong Hee (Sensors, 2022)
The Software‐Defined Networking (SDN) paradigm has transferred network intelligence from network devices to a centralized controller. Controllers are distributed in a network to eliminate a single point of failure (SPOF) and improve reliability and balance load. In Software‐Defined Internet of Things (SD‐IoT), sensors exchange data with a controller on a regular basis. If the controllers are not appropriately located in SD‐IoT, the E2E latency between the switches, to which the sensors are connected, and the controller increases. However, examining the placement of controllers in relation to the whole network is not an efficient technique since applying the objective function to the entire network is a difficult operation. As a result, segmenting the network into clusters improves the efficiency with which switches are assigned to the controller. As a result, in this research, we offer an effective clustering strategy for controller placement in SDN that leverages the Analytical Network Process (ANP), a multi‐criteria decision‐making (MCDM) scheme. The simulation results demonstrated on real Internet topologies suggest that our proposed method outperforms the standard k‐means approach in terms of E2E delay, controller‐to‐controller (C2C) delay, the fair allocation of switches in the network, and the communication overhead.
Keywords: Analytical network process; Controller placement problem; Controller placements; Effective approaches; K-means; Network intelligence; Network process; Openflow; Placement problems; Software-defined networkings; ANP; controller placement problem; k‐means; OpenFlow; SDN